WOMAC and SF-36: instruments for evaluating the health-related quality of life of elderly people with total hip arthroplasty. A descriptive study - Rampazo-Lacativa, Mariana Kátia; Santos, Ariene Angelini dos; Coimbra, Arlete Maria Valente; D’Elboux, Maria José (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVES: Quality-of-life results have increasingly been evaluated among patients undergoing joint replacements. The objective of this study was to compare two assessment instruments for health-related quality of life (one generic and the other specific), among elderly patients undergoing total hip arthroplasty. DESIGN AND SETTING: Cross-sectional descriptive study in a reference hospital in the region of Campinas. METHODS: The subjects were 88 elderly outpatients aged 60 years or over who underwent primary to-tal hip arthroplasty. Two instruments for assessing health-related quality of life were applied: the generic Medical Study 36-item Short-Form Health Survey (SF-36) and the specific Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Cronbach’s alpha and the ceiling and floor effects of the instru-ments were evaluated. RESULTS: The scores from both instruments showed that issues of a physical nature affected these elderly people’s quality of life most. The pain and stiffness dimensions of WOMAC showed ceiling effects and only the functional capacity and pain dimensions of the SF-36 did not show the ceiling effect. The SF-36 pre-sented floor effects in the dimensions of physical and emotional aspects. Cronbach’s alpha was considered satisfactory in both instruments (α > 0.70). CONCLUSIONS: The floor and ceiling effects that were observed suggest that these instruments may present some limitations in detecting changes to the majority of the SF-36 dimensions, except for func-tional capacity and pain, and to the pain and stiffness dimensions of WOMAC, when applied to elderly people with total hip arthroplasty.